Foreign Experience in Selling Products: Lessons and Insights (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In the globalized economy, the dynamics of selling products have evolved significantly due to the influence of foreign experiences. This article explores various foreign strategies, techniques, and approaches employed in selling products, highlighting the lessons and insights that can be gleaned from these experiences. By examining diverse cultural, technological, and market-related perspectives, we aim to provide a comprehensive overview of how foreign practices can inform and enhance domestic sales efforts.